Implementation and Effectiveness of Drug Abuse Program (SAJADAH) Among Students at Secondary Schools in the Kota Kinabalu, Sabah - Wan Anor Wan Sulaiman; Wan Nur Fatini Wan Anor; Wan Nazilah Wan Othman; Adi Fahrudin (Asian Social Work Journal, 2018)
This study is conducted to determine the extent to which the drug abuse programs are implemented (SEJADAH) by teachers and counselors are affected students in schools at the Kota Kinabalu, Sabah. The subjects have 150 students from form 1 to 5, and 96 regular teachers and counselor. A set of questionnaires which is divided into three sections, part A contains student biographical information, section B contains items about the effects of the program on students and section C contains items about program implementation by teachers and school staff. Descriptive analysis was used to analyze the data and found that 124 students considered the program drug abuse (SAJADAH) has a good effected on them. For the implementation stage, total of 58 teachers feel that the program is very effective.